Less invasive off-pump implantation of axial flow pumps in chronic ischemic heart failure: survival effects - Ghodsizad, Ali; Kar, Bisjwit J.; Layolka, Pranov; Okur, Abdullah; Gonzales, Jose; Bara, Christoph; Ungerer, Matthias; Karck, Matthias; Gregoric, Igor D.; Ruhparwar, Arjang (The journal of heart and lung transplantation, 2011)
Background - Off-pump implantation of left ventricular assist device (LVAD) axial or centrifugal flow pumps in patients with low ejection fraction (EF) is of major clinical relevance. In addition, all pre-clinical, long-term implantations performed so far have been carried out in healthy animals, but this does not reflect the eventual clinical setting. In this study we established a new technique using a miniaturized axial flow pump in sheep with chronically ischemic myocardium. - Methods - Sheep (n = 15) underwent intracoronary sphere injection to create chronic ischemic heart failure. Reduced EF was assessed using transesophageal echocardiography. All animals underwent implantation of a new miniaturized axial flow pump via an extraperitoneal, subcostal surgical approach. - Results - Our technique allows easy exposure of the diaphragmatic surface of the heart and the descending aorta. Ten animals (range 65 to 78 kg) underwent off-pump implantation 30 (range 25 to 33) days after intracoronary sphere injection. All animals had significantly reduced EF (25 ± 4.8%) and were receiving high doses of inotropic agents to maintain cardiac function. Nine animals survived the surgical procedure. The average 12-hour blood loss was 435 ml. Cardiac index improved significantly in all animals. The procedure time was not extended by any adverse events (60 to 145 minutes). - Conclusions - The extraperitoneal, subcostal surgical approach is less invasive than a median sternotomy and allows centrifugal or axial to be implanted quickly and without cardiopulmonary bypass (CPB). Avoiding CPB and an extensive mediastinal dissection can help to decrease significantly the number of complications in patients with end-stage organ failure.
Gesehen am 15.11.2023